Cryptosporidium parvum hijacks a host’s long noncoding RNA U90926 to evade intestinal epithelial cell-autonomous antiparasitic defense - Graham, Marion L.; Li, Min; Gong, Ai-Yu; Deng, Silu; Jin, Kehua; Wang, Shuhong; Chen, Xian-Ming (Frontiers in Immunology, 2023)
Cryptosporidium is a zoonotic apicomplexan parasite that infects the gastrointestinal epithelium and other mucosal surfaces in humans. It is an important opportunistic pathogen in AIDS patients and a leading cause of infectious diarrhea and diarrheal-related death in children worldwide. The intestinal epithelial cells provide the first line of defense against Cryptosporidium infection and play a central role in activating and regulating the host antiparasitic response. Increasing evidence suggests that long noncoding RNAs (lncRNAs) participate in host-pathogen interactions and play a regulatory role in the pathogenesis of diseases but the underlying molecular mechanisms are not fully understood. We previously identified a panel of host lncRNAs that are upregulated in murine intestinal epithelial cells following Cryptosporidium infection, including U90926. We demonstrate here that U90926 is acting in a pro-parasitic manner in regulating intestinal epithelial cell-autonomous antiparasitic defense. Inhibition of U90926 resulted in a decreased infection burden of the parasite while overexpression of U90926 showed an increase in infection burden in cultured murine intestinal epithelial cells. Induction of U90926 suppressed transcription of epithelial defense genes involved in controlling Cryptosporidium infection through epigenetic mechanisms. Specifically, transcription of Aebp1, which encodes the Aebp1 protein a potent modulator of inflammation and NF-κB signaling, was suppressed by U90926. Gain- or loss-of-function of Aebp1 in host epithelial cells caused reciprocal alterations in the infection burden of the parasite. Interestingly, Cryptosporidium carries the Cryptosporidium virus 1 (CSpV1), a double stranded (ds) RNA virus coding two dsRNA fragments, CSpV1-dsRdRp and CSpV1-dsCA. Both CSpV1-dsRdRp and CSpV1-dsCA can be delivered into infected cells as previously reported. We found that cells transfected with in vitro transcribed CSpV1-dsCA or CSpV1-dsRdRp displayed an increased level of U90926, suggesting that CSpV1 is involved in the upregulation of U90926 during Cryptosporidium infection. Our study highlights a new strategy by Cryptosporidium to hijack a host lncRNA to suppress epithelial cell-autonomous antiparasitic defense and allow for a robust infection.